2009
DOI: 10.1016/j.cellimm.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A threshold level of TLR9 mRNA predicts cellular responsiveness to CpG-ODN in haematological and non-haematological tumour cell lines

Abstract: Abstract:The human toll like receptor 9 (TLR9) detects differences between microbial and host DNA, based on unmethylated deoxycytidyl deoxyguanosine dinucleotide (CpG) motifs, leading to activation of both innate and adaptive immune mechanisms. The synthetic TLR9 agonist, CpG-ODN, can substitute for microbial DNA in these responses, and is in clinical trials as an immunomodulatory agent in diseases as diverse as infections, cancer and allergic disorders. Human TLR9 is expressed on cells of haematopoietic origin Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Our studies confirmed the feasibility of using CpG(A)-siRNAs for targeting human TLR9-expressing cells such as pDCs, mDCs, B cells, and several myeloid and B-cell malignancies. [25][26][27][37][38][39] We have demonstrated that although TLR9 Ϫ cells such as monocytes are still able to quickly internalize CpG(A)-siRNA, in the absence of TLR9 expression, conjugates do not induce RNAi. Our independent studies delineating the molecular mechanism of intracellular CpG-siRNA processing suggest that TLR9 may in fact participate For personal use only.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our studies confirmed the feasibility of using CpG(A)-siRNAs for targeting human TLR9-expressing cells such as pDCs, mDCs, B cells, and several myeloid and B-cell malignancies. [25][26][27][37][38][39] We have demonstrated that although TLR9 Ϫ cells such as monocytes are still able to quickly internalize CpG(A)-siRNA, in the absence of TLR9 expression, conjugates do not induce RNAi. Our independent studies delineating the molecular mechanism of intracellular CpG-siRNA processing suggest that TLR9 may in fact participate For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…33 The mechanism of STAT3 activation by class-B CpGODNs in human hematopoietic cells is likely to depend on up-regulation of cytokines such as IL-6 and IL-10, as shown in this and other studies. 23,26,32 The signaling cross-talk within the tumor microenvironment further enhances STAT3 signaling, dampening the immunostimulatory activity of TLR agonists. 33 In contrast, in the present study, we did not detect increased levels of STAT3-inducing cytokines in human PBMCs cultured with unconjugated CpG(A) ODNs or CpG(A)-siRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, these data point to a specific mechanism, in which the threshold RLT2 level in 4MS condition is not sufficient to activate phas-GUS expression in leaves, and suggest that Pv-ALF-dependent induction of RLT2 is necessary to trigger phas-GUS expression. A similar threshold mechanism for the basal level of p53 and toll like receptor 9 expression has recently been described for the activation of apoptosis and immune responses in human cells (Assaf et al, 2009;Kracikova et al, 2013).…”
Section: Rlt2 and Ail5 Are Required For Efficient Activation Of Phas-mentioning
confidence: 99%